Many-Faced Carnelian: The History of the Names of the Stone in the Russian Language Tradition - Kuchko, Valeria S. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2024)
This article studies the history behind the nominations of carnelian that have existed at different times within the Russian language tradition. They are loans from the ancient Greek language сардион, сардий, сардоних and сардоникии; Western European loans of Modern times карнеол, корналин; and the word сердолик which is native, but in many respects formally “induced” by the appearance of loanwords that already existed in the language. The fact of the multiplicity of nominations of this stone is due to several reasons: the antiquity of humankind’s acquaintance with this stone and the occurrence of its mentions in ancient texts that influenced the formation of the book culture of Old Rus’; the imported origin of the stone and only very late discovery of its home deposits; a specific linguistic and cultural situation that arose during the formation of the Russian scientific terminological system, when there was competition between the original names of the mineral and new Western European analogues, acquaintance with which occurred through the translation of mineralogical treatises. The article describes the factors that create the specifics of the linguistic history of carnelian, which are in different combinations characteristic of the whole area of the history of mineralogical names. The author comments on the time of the appearance of borrowed names of carnelian in the Russian language, their sources, the difference in the sphere of use, and semantic shades. Also, the article provides data on the time and reasons for the occurrence of the word сердолик, as well as its motivation based on intra-linguistic and extralinguistic factors, the existence of terminological parallelism with the participation of different names of carnelian, and competition between native and borrowed names.